2021
DOI: 10.5455/aim.2021.29.59-64
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Level Laser Therapy (LLLT) on Serum Values of Interleukin 6 (IL-6) in Patients with Periodontitis and Type 2 Diabetes Mellitus (T2DM)

Abstract: Background: In patients with T2DM, the therapeutic effects of conservative treatment are quite limited, and there is a need for additional therapeutic procedures to achieve the desired satisfactory and solid effect. Low-level laser therapy (LLLT) has an anti-inflammatory effect, and is used to heal lesions. This mechanism is realized through inhibition of lipopolysaccharides (LPS), so it can be used in the treatment of periodontal disease in patients with diabetes. Objective: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…At the same time, they also stimulate the host and activation of in ammatory cells and immune cells, which triggered systemic in ammation and immune response, leading to upregulation of in ammatory mediators' level and acute phase proteins level [12]. Il-6, IL-1β, and IL-8 were all in ammatory mediators that regulated the immune response in the host body to microbial infection and played a central role in the destruction of periodontal tissues [13][14][15]. In ammatory indicators such as IL-6, IL-1β, and IL-8 with an abnormal upward trend would aggravate the injury degree of vascular endothelial cells and further aggravate the in ammatory response of periodontal tissues, which may reduce the e ect of drug treatment and increase the risk of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, they also stimulate the host and activation of in ammatory cells and immune cells, which triggered systemic in ammation and immune response, leading to upregulation of in ammatory mediators' level and acute phase proteins level [12]. Il-6, IL-1β, and IL-8 were all in ammatory mediators that regulated the immune response in the host body to microbial infection and played a central role in the destruction of periodontal tissues [13][14][15]. In ammatory indicators such as IL-6, IL-1β, and IL-8 with an abnormal upward trend would aggravate the injury degree of vascular endothelial cells and further aggravate the in ammatory response of periodontal tissues, which may reduce the e ect of drug treatment and increase the risk of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 16 studies were conducted to evaluate the impact of PBM on chronic periodontitis in humans ( 34 40 , 141 149 ) ( Table 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…10 The photo-biological effects of PBMT and their interference with the immune system are very well known. [11][12][13][14] Studies also reported the effect of PBMT on cytokine (IL-4, IL-10, or IL-13) and chemokine (CCL2, CXCL10, and TNF-α) production and elucidate the mechanism via histone modification of cytokine expression in monocytes, as well as enhanced cytokine and chemokine expression in mRNA and protein levels. 15 The effect of PBMT on proinflammatory cytokines or other mediators and their important role in the pathophysiology of inflammatory diseases such as osteoarthritis (OA) has also been reported.…”
Section: Introductionmentioning
confidence: 99%